Identifikasi Sektor Ekonomi Unggulan di Provinsi Jawa Barat - Ghania, Sarah; Khatimah, Khusnul; Azrimultiya , Viyolanda (Journal of Development Economics and Digitalization, 2025)
Penelitian ini bertujuan untuk mengidentifikasi sektor-sektor ekonomi unggulan di Provinsi Jawa Barat. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kuantitatif dengan menggunakan data sekunder yakni data PDRB Jawa Barat dan PDB Indonesia tahun 2010-2023 yang diperoleh dari Badan Pusat Statistik. Alat analisis pada penelitian ini adalah Location Quitoent (LQ) dan Dynamic Location Quotient. Hasil penelitian menunjukkan terdapat beberapa lapangan usaha yang menjadi sektor unggulan di Jawa Barat dimana sektor-sektor tersebut memiliki nilai LQ>1 dan DLQ>1. Sektor unggulan berdasarkan hasil perhitungan LQ dan DLQ antara lain sektor industri pengolahan, pengadaan listrik dan gas, perdagangan besar dan eceran;reparasi mobil dan sepeda motor, transportasi dan pergudangan, jasa kesehatan dan kegiatan sosial, jasa lainnya. Abstract West Java is one of the provinces that makes a significant contribution to Indonesia's GDP. However, despite the substantial contribution of its economic sectors, this has not translated into improved welfare for its population. This is reflected in several economic indicators, such as per capita income and the open unemployment rate, which have not reached optimal levels. This study aims to identify the leading economic sectors in West Java in order to improve the welfare of its population. The research employs a descriptive quantitative approach using secondary data, specifically GRDP data for West Java and GDP data for Indonesia from 2010 to 2023, sourced from the Central Statistics Agency. The analytical tools applied in this study are Location Quotient (LQ) and Dynamic Location Quotient (DLQ). The findings reveal that several sectors are considered leading in West Java, with these sectors exhibiting LQ and DLQ values greater than 1. These leading sectors, based on the LQ and DLQ calculations, include manufacturing, electricity and gas supply, wholesale and retail trade; repair of motor vehicles and motorcycles, transportation and warehousing, health and social activities, and other services. Keywords: West Java, Leading Sectors, Location Quotient, Dynamic Location Quotien